2019
DOI: 10.1590/1516-4446-2018-0108
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional neuroimaging studies in generalized anxiety disorder: a systematic review

Abstract: Objectives:Brain imaging studies carried out in patients suffering from generalized anxiety disorder (GAD) have contributed to better characterize the pathophysiological mechanisms underlying this disorder. The present study reviews the available functional and structural brain imaging evidence on GAD, and suggests further strategies for investigations in this field.Methods:A systematic literature review was performed in PubMed, PsycINFO, and Google Scholar, aiming to identify original research evaluating GAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 146 publications
(171 reference statements)
1
39
0
4
Order By: Relevance
“…Not only structural but also functional overlaps are apparent between AN and other psychiatric disorders. For instance, the hyperactivation of the PFC and the amygdala which are commonly reported in AN, are also features of the generalized stress disorder [ 163 ]. In addition, as mentioned before, altered functional connectivity between and within core RSNs characterizes many other psychiatric disorders, including OCD [ 162 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only structural but also functional overlaps are apparent between AN and other psychiatric disorders. For instance, the hyperactivation of the PFC and the amygdala which are commonly reported in AN, are also features of the generalized stress disorder [ 163 ]. In addition, as mentioned before, altered functional connectivity between and within core RSNs characterizes many other psychiatric disorders, including OCD [ 162 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it has been recently suggested that BOLD responses from emotional tasks, especially from limbic regions, have poor psychometric properties (e.g., test-retest reliability) [ 7 , 8 ]. While the current review found generally consistent findings concerning the amygdala, this warrants attention for future task-based fMRI investigations, as the issue of reliability becomes exacerbated by small sample sizes [ 88 ].…”
Section: Factors Contributing To the Mixed Findings In Task-based mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI), in particular, offers a non-invasive means to measure diverse properties of the human brain, including regional volume, functional responsivity to psychological tasks, functional architecture at rest, and connectivity. Naturally, an abundance of MRI studies of GAD has been made available over the past 20 years (see [ 6 , 7 ] for recent reviews of the literature).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this context, the present issue of the Brazilian Journal of Psychiatry publishes a systematic review of brain imaging studies in patients with generalized anxiety disorder (GAD) 8. This review provides some inspiring data, despite the methodological heterogeneity of the included studies.…”
mentioning
confidence: 88%